Anti-leishmaniasis effect of Staphylococcus aureus Protein A on the size of the lesion and parasitic load - Zahra Tavalaei; Mehrdad Zeinalian; Hossein Khanahmad; Hossein Hejazi (Advanced Biomedical Research, 2023)
Background: Many studies in the past have evaluated the role of immune system boosters in the treatment of leishmania major infection. Protein A (PA) is one of the structural components in peptidoglycan cell wall of gram-negative bacteria such as staphylococcus aurous which functions as a stimulator in the cellular immune system. The present study aims to evaluate the anti-inflammatory effect of PA on the recovery of leishmania major infection. Materials and Methods: This study was conducted on 24 female Balb/c-infected mice. The experimental group received PA at a dose of 60 mg/kg for four weeks. There was no intervention for the negative control group; the third group received the solvent of PA and sterile H2O; and the positive control group received Amphotericin B at a dose of 1 mg/kg body weight. At the end of the treatment period, a real-time polymerase chain reaction (PCR) assay was performed to determine parasitic burden, and the size of the lesions was measured by caliper with an accuracy of 0.01 mm. Results: Results showed that PA did slightly decrease the wound spread and growth but not to an extent that can be considered statistically significant. Also, differences in cycle threshold (Ct) values between the treated group and the untreated group was not impressive. Conclusions: Although findings showed that PA isn't such a good candidate for leishmania treatment, it may still be suitable for therapies that use multiple drugs in combination to speed up the healing of leishmaniosis, an issue that merits evaluation in future studies.